2018
DOI: 10.1371/journal.pone.0205713
|View full text |Cite
|
Sign up to set email alerts
|

Bt eggplant (Solanum melongena L.) in Bangladesh: Fruit production and control of eggplant fruit and shoot borer (Leucinodes orbonalis Guenee), effects on non-target arthropods and economic returns

Abstract: Eggplant or brinjal (Solanum melongena) is a popular vegetable grown throughout Asia where it is attacked by brinjal fruit and shoot borer (BFSB) (Leucinodes orbonalis). Yield losses in Bangladesh have been reported up to 86% and farmers rely primarily on frequent insecticide applications to reduce injury. Bangladesh has developed and released four brinjal varieties producing Cry1Ac (Bt brinjal) and is the first country to do so. We report on the first replicated field trials comparing four Bt brinjal varietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 21 publications
0
34
1
Order By: Relevance
“…Previous studies on the impact of using Bt brinjal (see introduction) have shown virtually complete control of EFSB in Bangladesh without any disruption of non-target arthropods (Prodhan et al, 2018). In the Philippines, a similar level of control (Hautea et al, 2016) and lack of effect on non-target arthropods (Navasero et al, 2016) was observed.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previous studies on the impact of using Bt brinjal (see introduction) have shown virtually complete control of EFSB in Bangladesh without any disruption of non-target arthropods (Prodhan et al, 2018). In the Philippines, a similar level of control (Hautea et al, 2016) and lack of effect on non-target arthropods (Navasero et al, 2016) was observed.…”
Section: Discussionmentioning
confidence: 70%
“…This study also identified that farmers spent 61% less on pesticides compared to non-Bt brinjal farmers and experienced no yield losses due to the EFSB. In a 2-year study conducted by Prodhan et al (2018), all four Bt brinjal varieties provided virtually complete control of EFSB without the use of insecticides for EFSB control, and had higher gross returns than their non-Bt equivalents. A report by Ahmed et al (2019) evaluated the impacts of the Bt brinjal technology on production systems, marketability, and human health.…”
Section: Introductionmentioning
confidence: 99%
“…Cultivation of Bt-brinjal reduced labor and chemical costs. Prodhan et al (2018) compared the impacts of four Btbrinjal varieties and conventional brinjal. They found a 0-2% fruit infestation of FSB among the Bt-brinjal varieties versus a 36-45% infestation in conventional brinjal varieties.…”
Section: Benefits Of Bt-brinjal Cultivation By Farmersmentioning
confidence: 99%
“…After eight years of breeding and testing, in 2013 four varieties were approved for cultivation by Bangladesh's National Committee on Biosafety (APAARI 2018). In 2014, 20 farmers received seedlings of the four varieties of Bt brinjal from the Ministry of Agriculture to grow on a trial basis (Shelton et al 2018). Three observational studies, one with approximately 100 farmers 1 , a second on a research farm (Prodhan et al 2018), and a third (Rashid, Hasan, and Matin 2018) with a larger sample size (505 Bt brinjal farmers and 350 farmers growing conventional brinjal) all provided evidence that Bt brinjal can reduce FSB infestation, requires fewer pesticides, and results in higher yields with lower production costs.…”
Section: Introductionmentioning
confidence: 99%